Fungal Spoilage of Coconut (Cocos nucifera L.) Fruits During Storage and the Growth Differential of Isolates on Selected Amino Acids and Carbohydrates - Okolie, P.N.; Obi, C.L.; Uaboi-Egbenni, P.O. (Pakistan Journal of Nutrition, 2011)
Husked and dehusked coconut fruits were stored at 10°C and 30°C for three months. The husked coconut fruits stored at both 10°C and 30°C and the dehusked coconut fruits stored at 10°C showed no evidence of microbial spoilage at the end of the three months storage period. However, dehusked coconut fruits stored at 30°C deteriorated. Aspergillus flavus and Aspergillus niger were the principal fungal agents associated with the spoilage. An investigation of the proximate composition of the dehusked fruits stored at 30°C indicated a marked significant difference in the percentage composition of moisture, protein, ascorbic acid and carbohydrate content of 3.97±0.28, 3.98±0.07, 0.01±0.002 and 9.27±1.02 respectively as against 46.82±0.43, 3.77±0.05, 2.48±0.15 and 11.89±0.22 obtained for dehusked coconut fruits prior to storage. These results suggest that the deterioration in nutritional composition was due to breakdown of protein and carbohydrate by the spoilage fungi. Further tests confirmed the ability of the isolated spoilage fungi to utilize the different carbohydrate and nitrogen sources as source of carbon and energy. Aspergillus flavus showed the ability to grow and utilize more of the various carbohydrate sources than Aspergillus niger, although the latter utilized lactose better. Both fungi showed evidence of growth and complete utilization of nearly all the nitrogen sources, except cysteine and L-glutamine, which could not support the growth Aspergillus niger. Likewise, cysteine and L-glutamine, in addition to D-β-phenylalanine could not support the growth of Aspergillus flavus.